2008
DOI: 10.1108/08876040810901855
|View full text |Cite
|
Sign up to set email alerts
|

An empirical test of the drivers of overall customer satisfaction: evidence from multivariate Granger causality

Abstract: Purpose -The purpose of this paper is to investigate whether customer-perceived service quality and expectation of service quality have causal impacts on overall customer satisfaction. Design/methodology/approach -Data on all the variables were elicited from the American Customer Satisfaction Index (ACSI), and these were analyzed using the Granger causality method. Findings -Satisfaction and perceived quality were positively related. Even though perceived quality did not Granger-cause satisfaction in the short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 82 publications
(63 reference statements)
0
11
0
2
Order By: Relevance
“…Ueltschy, Laroche, Eggert and Bindl, (2007) revealed while comparing US and Japan in context that high performance will lead towards high expectations which will eventually yield high customer satisfaction and high perceived service quality. Omachonu, Johnson and Onyeaso, (2008) explained that according to the American Customer Satisfaction Index (ACSI), customer expectations are evaluated by asking the customer to recall the level of quality they expected on the basis of their knowledge about service or goods and actual experience with a goods or services. Based on these basic questions, responses are obtained from the customer on the three basic questions given by Fornell et al, 1996, p. Hamer, (2006) advises the practitioners that the service performance received by consumers should exceed their expectations.…”
Section: Perceived Service Qualitymentioning
confidence: 99%
“…Ueltschy, Laroche, Eggert and Bindl, (2007) revealed while comparing US and Japan in context that high performance will lead towards high expectations which will eventually yield high customer satisfaction and high perceived service quality. Omachonu, Johnson and Onyeaso, (2008) explained that according to the American Customer Satisfaction Index (ACSI), customer expectations are evaluated by asking the customer to recall the level of quality they expected on the basis of their knowledge about service or goods and actual experience with a goods or services. Based on these basic questions, responses are obtained from the customer on the three basic questions given by Fornell et al, 1996, p. Hamer, (2006) advises the practitioners that the service performance received by consumers should exceed their expectations.…”
Section: Perceived Service Qualitymentioning
confidence: 99%
“…Penelitian terdahulu telah membuktikan bahwa kepuasan pelanggan diklasifikasikan menjadi dua jenis, yaitu overall satisfaction yang mungkin berasal dari beberapa pengalaman dan encounter satisfaction yang dihasilkan dari evaluasi interaksi tunggal dan diskrit Omachonu, Johnson, & Onyeaso, 2008).Penelitian ini berfokus pada pemahaman rapport dari encounter satisfaction, sedangkan overall satisfaction lebih sesuai untuk tujuan penelitian daripada encounter satisfaction. Service encounter dihasilkan dari beberapa hal seperti complaint handling (Gruber, Szmigin, & Voss, 2009), perceived service level (Sharma, Tam, & Kim, 2012), loyalty and word of mouth (Matos, Henrique, & Rosa, 2013), customer satisfaction merupakan variabel yang paling sering didiskusikan dalam literatur rapport (Fatima et al, 2015;Gremler & Gwinner, 2008;Macintosh, 2009).…”
Section: Gambar 1 Rerangka Konseptual Pengembangan Hipotesisunclassified
“…Additionally, satisfaction also influences financial successfulness of a company. There are numerous studies that confirmed positive effect of satisfaction on return on investment and profitability of a company (see, for example Anderson et al, 1994;Omachonu et al, 2008;Yeung & Ennew, 2000;Yu, 2007). The strategic meaning of satisfaction besides business benefits is also seen in how satisfaction represents such elements according to which basic business strategy has to be determined.…”
Section: Measuring Customer Satisfactionmentioning
confidence: 99%